Hearing Loss Secondary to Systemic Sclerosis Vasculopathy: Case Study with a Short Review - Bobeica C; Niculet E; Craescu M; Parapiru EL; Musat CL; Dinu C; Chiscop I; Nechita L; Stefanescu V; Stefanopol IA; Pelin AM; Nechifor A; et al. (Clinical, Cosmetic and Investigational Dermatology, 2022)
Carmen Bobeica,1,* Elena Niculet,1,2 Mihaela Craescu,1 Elena-Laura Parapiru,3,* Carmina Liana Musat,1,* Ciprian Dinu,4,* Iulia Chiscop,5,* Luiza Nechita,3,* Victorita Stefanescu,6,* Ioana Anca Stefanopol,1,7,* Ana Maria Pelin,8,* Alexandru Nechifor,3,* Gabriela Balan,3,9,10,* Alin Laurentiu Tatu2,3,11 1Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 2Multidisciplinary Integrated Center of Dermatological Interface Research MIC-DIR (Centrul Integrat Multidisciplinar de Cercetare de Interfata Dermatologica - CIM-CID), ‘Dunărea de Jos’ University, Galați, Romania; 3Clinical Medical Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 4Dental Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 5Clinical Surgical Department, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 6Medical Department, Faculty of Medicine and Pharmacy, Dunărea de Jos University, Galați, Romania; 7Department of Pediatrics, Clinical Emergency Hospital for Children “Sf. Ioan”, Galati, Romania; 8Department of Pharmaceutical Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, Galați, Romania; 9Department of Gastroenterology, “Sf. Apostol Andrei” County Emergency Clinical Hospital, Galați, Romania; 10Research Center in the Field of Medical and Pharmaceutical Sciences, “Dunărea de Jos” University, Galați, Romania; 11Dermatology Department, “Sf. Cuvioasa Parascheva” Clinical Hospital of Infectious Diseases, Galați, Romania*These authors contributed equally to this workCorrespondence: Elena Niculet; Mihaela Craescu, Department of Morphological and Functional Sciences, Faculty of Medicine and Pharmacy, “Dunărea de Jos” University, 35 Alexandru Ioan Cuza Street, Galați, 800008, Romania, Tel +40741398895 ; +40751869864, Email helena_badiu@yahoo.com; dr.craescumihaela@yahoo.roAbstract: Systemic sclerosis (SSc) is a collagenosis with a substrate of chronic inflammation, which is determined by autoimmunity. The pathogenesis of this disease involves microvasculopathy (small vessel pathology) followed by excessive cutaneous and visceral fibrosis. Although acoustic and vestibular impairment is not classified as being a secondary pathology of SSc, several studies have identified cases of SSc that associate hearing loss and especially vertigo and tinnitus. This paper presents data from the medical literature that have identified vestibular and auditory symptoms among patients with SSc, associating the clinical case presentation of a patient suffering from SSc, which is associated with hearing loss. The need for additional studies on larger groups of patients is underlined, in order to clarify the impact of vasculopathy and fibrosis on the acoustic and vestibular analyzer in patients with SSc.Keywords: systemic sclerosis, hearing loss, vasculopathy, fibrosis, capillaroscopy